Azobenzene‐Substituted Triptycenes: Understanding the Exciton Coupling of Molecular Switches in Close Proximity. Issue 38 (3rd June 2022) - Kunz, Anne; Oberhof, Nils; Scherz, Frederik; Martins, Leon; Dreuw, Andreas; Wegner, Hermann A.
Abstract: Herein, we report a series of azobenzene‐substituted triptycenes. In their design, these switching units were placed in close proximity, but electronically separated by a sp 3 center. The azobenzene switches were prepared by Baeyer–Mills coupling as key step. The isomerization behavior was investigated by 1 H NMR spectroscopy, UV/Vis spectroscopy, and HPLC. It was shown that all azobenzene moieties are efficiently switchable. Despite the geometric decoupling of the chromophores, computational studies revealed excitonic coupling effects between the individual azobenzene units depending on the connectivity pattern due to the different transition dipole moments of the π→π* excitations. Transition probabilities for those excitations are slightly altered, which is also revealed in their absorption spectra. These insights provide new design parameters for combining multiple photoswitches in one molecule, which have high potential as energy or information storage systems, or, among others, in molecular machines and supramolecular chemistry. Abstract : Switchable host system : Azobenzenes have been attached to a triptycene scaffold in the meta position. Isomerization experiments revealed efficient switching of azobenzene moieties together with the build‐up of a cavity in the all‐ Z conformation of the C 3v ‐symmetric trisazobenzene‐triptycene; this makes this molecule interesting as a switchable host system. Moreover, computational studies indicated excitonic coupling resulting in different transition probabilities of π–π* excitations.